Nonverbal Communication Between Mother and Child in the Novel Si Anak Spesial by Tere Liye - Eka Nova Ali Vardani; Yeni Mardiyana Devanti (Universitas Muhammadiyah Malang, 2025)
Communication in the family is important in shaping the child's character. Communication must be maintained from when the child is in the womb until adulthood. This study is a library study with the researcher as the main instrument. The qualitative description method was chosen because it focuses on the meaning, context, and interpretation of non-verbal interactions implied in the narrative. The research procedure includes the planning, implementation, and completion stages. From the data presented, ten forms of non-verbal communication between mother and child were found in the novel: swallowing saliva, wiping the nose, gripping the arm, scratching the leg, nodding, and shaking the head. The results of the study on non-verbal communication between mother and child in the novel Si Anak Spesial by Tere Liye suggest several suggestions that can be put forward. For further research, it is hoped that it can expand the study by analysing non-verbal communication in various other literary works to see broader patterns in family relationships. In addition, this research can be developed with an interdisciplinary approach, such as psychology or sociology, to understand the impact of non-verbal communication on the development of children's character in real life. For readers, especially parents and educators, this study is expected to increase awareness of the importance of non-verbal communication in building emotional closeness with children.